PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF STUDENTS RESEARCH SKILLS IN THE USE OF THE LABORATORY IN BIOLOGY LESSONS - Tadjiyev, X.M. (PT. Antis International Publisher, 2025)
Objective: To examine the methodological foundations underpinning the formation of the competence